Community Views on the Implementation of Government Employee Recruitment Policy with Madrasah Teacher Employment Agreements - Wahyudin Noor; Muhamad Muhamad (Program Studi Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2025)
This study aims to analyze the factors that influence the implementation of the Government Employee madrasah teacher recruitment policy in the Work Agreement and its implications for the effectiveness of the policy. This study uses a qualitative approach with a policy study method involving document analysis and interviews with relevant stakeholders. The results of the study indicate that applicable regulations have implemented this policy. However, there are still obstacles in planning the formation and placement of educators that hinder the optimization of the policy. Further discussion reveals that although this policy provides job certainty for madrasah teachers, the less-than-optimal implementation process can impact the quality of education. Therefore, improvements are needed in the mechanism for planning the formation and distribution of teachers to increase the recruitment policy's effectiveness. Further research is recommended to explore the factors causing the mismatch of formation and its impact on the quality of learning in madrasahs.